Pineapple Among the Indigenous Nambikwara: Early Twentieth Century Photographic Documentation from Central Brazil - Coimbra, Carlos E. A.; Welch, James R. (Ethnobiology Letters, 2020)
In the region that is today Brazil, presence of pineapple in the food of Indigenous peoples was noted early by the Portuguese and other European explorers, who described the presence of the plant in Indigenous gardens and around villages along the Atlantic coast and in the interior. The objective of this paper is to contribute to the ethnobotany and history of pineapple in South America, particularly Central Brazil, based on the first known photographic documentation of the use of pineapple in the diet of an Indigenous society: the Nambikwara in the northwestern region of the State of Mato Grosso, Brazil. The pineapple’s presence in Nambikwara villages immediately caught the attention of the early explorers and fermented Nambikwara “pineapple wine” enjoyed enormous success. The photographic record presented here was produced on the occasion of one of the first scientific expeditions sponsored by the Brazilian government in the early twentieth century, the Commission for the Construction of Telegraph Lines from Mato Grosso to Amazonas (better known as the “Rondon Commission”). All photos presented here were taken by Major Thomas Reis during a visit to the Nambikwara-Mamaindê village, in the Cabixi River region, in northern Mato Grosso, during the expedition undertaken from 1913 to 1914. They show many details of how pineapples (Ananas ananassoides) are processed, including the familiar setting of a child playing beside her working mother. As these four images suggest, unexplored archival materials offer great potential for conducting visual historical ethnobotanical studies of topics that are otherwise invisible in the academic record.